Health Inequalities in the British Nursing Workforce - Ball, William; Kyle, Richard; Atherton, Iain; Dougall, Nadine (International Journal of Population Data Science, 2018)
Background Average health in the UK is improving, yet geographical inequalities in health persist. The relative difference between the least and most deprived is also growing. Recent policy interventions to reduce these inequalities have not been effective. Methods This work compares Self-Rated Health using the ONS LS and SLS linked to an adjusted UK-consistent small-area Deprivation measure. This study aims to compare Nurses to the general population to assess whether they also exhibit a social gradient in health. Using a single occupational group adjusts for potential confounders and tests whether characteristics of Nurses, such a good health literacy, degree education and above average income, are protective against inequalities. Results In Scotland, Nurses are more likely to be older, female, homeowners who live in less deprived areas with better Self-Rated Health than Non-Nurses. We will test whether the social gradient in health is observed for this occupational group. Forthcoming results from cross-national analysis will be presented at conference following disclosure checks. Conclusion The relationship between area deprivation and health may remain even in relatively privileged groups. Results from this study may inform recommendations to improve the effectiveness of policy aimed at improving population health and reducing socio-economic inequalities in health